NOVEL RP-HPLC METHOD FOR THE QUANTIFICATION OF ABIRATERONE ACETATE - SG Vasantharaju (Journal of Global Pharma Technology, 2016)
Simple, rapid, accurate and specific RP-HPLC method has been developed for quantitative estimation ofAbiraterone acetate in bulk and tablet. Separation was attained by using Acclaim C18 column (50mm x4.6 mm, 5) at 25C and 80:20 v/v acetonitrile:ammonium acetate buffer(10mM) of pH 6.0 with flow rateof 1ml/min as mobile phase and the drug was detected at 254 nm. Analytical method was said to belinear over a range of 0.125-60 g/ml with correlation constant of 0.999. Method was appeared to beprecise, robust and rugged. LOD and LOQ were found to be 10 ng/ml and 50 ng/ml respectively and themean recovery value as 100.52%.Stability indicating capability of this method has been demonstrated byanalyzing stressed samples of drug and found labile to acidic, alkaline, oxidative, thermal and photolyticconditions. Above method was applied for the estimation in API, formulation and dissolution testing ofthe dosage form. Percentage assay of the formulation was found to be 101.66%w/w. Drug released to anextent of 85.29% at 30 minutes as per FDA published method. Thus, the analytical procedure is reliableand offers advantage in terms of speed; so could be effectively used for the routine quality controlpurpose.